2010
DOI: 10.1089/met.2009.0127
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Plasma Leptin Levels and Chronic Complication in Patients with Type 2 Diabetes Mellitus

Abstract: Our data suggest that obesity, hypertension, dyslipidemia, and metabolic syndrome in T2DM were associated with increased plasma leptin levels. We conclude that plasma leptin levels may not be strongly associated with microangiopathy and macroangiopathy in T2DM individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 36 publications
4
63
5
Order By: Relevance
“…Accordind to kopeisy et al, leptin levels are significantly elevated in patients with microalbuminuria and macroalbuminuria compared to patients with normoalbuminuria 11,12 . Studies have also stated higher leptin levels in patients with diabetic neuropathy 13 . Microvascular complications of diabetes mellitus are principally due to vascular inflammation and leptin has deleterious effects on vasculature.…”
Section: Discussionmentioning
confidence: 97%
“…Accordind to kopeisy et al, leptin levels are significantly elevated in patients with microalbuminuria and macroalbuminuria compared to patients with normoalbuminuria 11,12 . Studies have also stated higher leptin levels in patients with diabetic neuropathy 13 . Microvascular complications of diabetes mellitus are principally due to vascular inflammation and leptin has deleterious effects on vasculature.…”
Section: Discussionmentioning
confidence: 97%
“…(Gariano et al 2000. However, in other studies the authors reported no association between leptin and the development and progression of retinopathy (Sari et al, 2010).…”
Section: Leptinmentioning
confidence: 86%
“…It also impairs endothelial cell functions, stimulates the proliferation of glomerular endothelial cells, increases TGF-β1 synthesis and collagen type IV production and upregulates surface TGF-β type II receptors through signal transduction pathways involving PI3K (phosphoinositide 3-kinase) [17]. In human settings, several reports demonstrated that serum leptin levels correlated with proteinuria in Type 2 DM [26]; however, others reported no association of serum leptin levels and the presence of DN [27]. Leptin also stimulates hypertrophy, but not proliferation of cultured rat mesangial cells, and infusion of leptin for 3 weeks into normal rats promotes the development of glomerulosclerosis and proteinuria [17].…”
Section: Hormonal Factors and Adipokinesmentioning
confidence: 99%